Influence of anatomical barriers on maxillary incisor root resorption after orthodontic treatment with premolar extractions - Antonio Geraldo de Oliveira; Fabiana Guilhermina Ferreira Castro (Dental Press Editora, 2012)
INTRODUCTION: Apical root resorption is a frequent and occasionally critical problem in orthodontic patients undergoing induced tooth movement. One of the factors that might influence prognosis, especially in maxillary incisors, which most frequently present resorptions, are the so-called the anatomical barriers; that is, proximity of the buccal and palatal cortical bones to the maxillary incisor roots. OBJECTIVE: The purpose of this research was to investigate whether patients with excessive vertical growth really present a small distance between the alveolar cortical bones and the maxillary incisor roots, and whether there is a correlation between this distance and the root resorption index in comparison with patients presenting horizontal growth. METHODS: The sample comprised orthodontic records of 18 patients with extraction planning of first maxillary premolars and treatment by the standard and/or preadjusted edgewise brackets. Their initial and final periapical radiographs were evaluated to determine the amount of root resorption that occurred. RESULTS: On the palatal side, patients with excessive vertical growth (Group 2 - SN-GoGn > 43º) showed a narrower alveolar bone than the horizontal growth patients (Group 1 - SN-GoGn < 29º). However, the distance between the buccal cortical bone and the central incisor root apex showed no significant difference between Groups 1 and 2; CONCLUSIONS: It was concluded that there are no correlations between the proximity of buccal cortical bone, maxillary incisor roots and the root resorption index.